Low‐Temperature Operation of High‐Efficiency Germanium Quantum Dot Photodetectors in the Visible and Near Infrared. Issue 3 (4th October 2017) - Siontas, Stylianos; Li, Dongfang; Liu, Pei; Aujla, Sartaj; Zaslavsky, Alexander; Pacifici, Domenico
Abstract : The temperature‐dependent operation of high efficiency Ge quantum dot (QD) photodetectors (PDs) is reported, that shows spectral responsivity of 1.2 A W −1, internal quantum efficiency (IQE) of 228% and signal‐to‐noise ratio (SNR) equal to 7 × 10 6 at a wavelength of 640 nm for 12 μW of incident power. The performance of these photodetectors can be improved by reducing the operating temperature, especially at low incident power. For instance, at 10 nW of 640 nm illumination power, lowering temperature from 300 to 100 K improves SNR from 2 × 10 4 to 2 × 10 5 and specific detectivity D* from 1.2 × 10 11 to 2 × 10 13  cm Hz 1/2  W −1 . This enhanced performance is attributed to saturation of the charging process within the QD layer, that leads to longer hole lifetimes and IQE exceeding 22 000%. Also, the near‐infrared performance of these PDs is reported, finding that below 200 K there is a significant near‐IR photocurrent (three orders of magnitude larger than the dark current at 1100 nm and two orders of magnitude larger than the dark current at 1300–1550 nm, where only the Ge QDs contribute to optical absorption), leading to operational PDs, albeit at lower D *. Abstract : Germanium quantum dot photodetectors are fabricated via co‐sputtering on silicon substrates exhibiting strong photoresponse in the visible and near‐infrared. Operating at cryogenic temperatures (100 K) shows an enhancement in performance, specifically at lower incident power, leading to significantly increased SNR, specific detectivity and internal gain in excess of 22 000%, attributed to saturation of the charging process within the quantum dot layer.